Fluorescent carbon dots from mono- and polysaccharides: synthesis, properties and applications - Hill, Stephen; Galan, M. Carmen (Beilstein Journal of Organic Chemistry, 2017)
Fluorescent carbon dots (FCDs) are an emerging class of nanomaterials made from carbon sources that have been hailed as potential non-toxic replacements to traditional semiconductor quantum dots (QDs). Particularly in the areas of live imaging and drug delivery, due to their water solubility, low toxicity and photo- and chemical stability. Carbohydrates are readily available chiral biomolecules in nature which offer an attractive and cheap starting material from which to synthesise FCDs with distinct features and interesting applications. This mini-review article will cover the progress in the development of FCDs prepared from carbohydrate sources with an emphasis on their synthesis, functionalization and technical applications, including discussions on current challenges.
Keywords: fluorescent carbon dots; monosaccharides; nanomaterials; nanotechnology applications; polysaccharides